Real exchange rates, dollarization and industrial employment in Latin America - Arturo Galindo; Alejandro Izquierdo; José Manuel Montero (Inter-American Development Bank, Research Department, 2006)
We use a panel dataset on industrial employment and trade for 9 Latin American countries for which liability dollarization data at the industrial level is available. We test whether real exchange rate fluctuations have a significant impact on employment, and analyze whether the impact varies with the degree of trade openness and liability dollarization. Econometric evidence supports the view that real exchange rate depreciations can impact employment growth positively, but this effect is reversed as liability dollarization increases. In industries with high liability dollarization, the overall impact of a real exchange rate depreciation can be negative.
Keywords: E24; F31; F34; G32; 330; Manufacturing employment; Real exchange rates; Debt composition; Balance sheet effects; Industrielle Beschäftigung; Kaufkraftparität; Auslandsverschuldung; Währungssubstitution; Lateinamerika